MAGICAL REALISM ELEMENTS IN DIANNA WYNNE JONES’ NOVEL HOWL’S MOVING CASTLE - Juwairina, Salsa Ismil; Ekalestari, Susi (JOURNAL OF LANGUAGE, 2024)
This study offers an in-depth analysis of the elements of magical realism in Diana Wynne Jones' novel Howl's Moving Castle. The research focuses on specific instances of magical realism, examining their impact on character development, relationships, and personal growth throughout the narrative. Using Wendy B. Faris' theoretical framework of magical realism, this study aims to reveal how fantastical elements shape character interactions and influence readers’ perceptions of the genre’s unique attributes. A qualitative descriptive method is employed to identify three core elements of magical realism within Howl's Moving Castle: the irreducible element, the phenomenal world, and the disruption of time, space, and identity. These components are shown to significantly impact character dynamics and personal transformations, highlighting how magical realism blends reality with myth to explore complex human experiences and social themes. The findings provide valuable insights into the narrative techniques and thematic depth of the genre, enriching the understanding of magical realism’s role in literature.